Infection Control Practices among Dental Practitioner in a Public Sector Tertiary Care Hospital During Second Wave of Covid-19 Pandemic in Karachi, Pakistan (Medical Forum Monthly, 2021)
Objective: To determine the infection control practices among dental practitioner in a public sector tertiary care hospital during a second wave of COVID-19 pandemic in Karachi, Pakistan.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Jinnah Sindh Medical University (JSMU) and Jinnah Postgraduate Medical Center (JPMC) from December 2020 to February 2021.Materials and Methods: An online survey was conducted and a self-prepared questionnaire was disseminated in closed social media group of the two institutes. The questionnaire included following components; consent form, patients screening, use of personal protective equipment (PPE), hand hygiene practices, environmental cleaning, injection safety precautions. Practices were considered as acceptable if the score was ≥80% of the total questionnaire score based on Bloom’s threshold.Results: Most of the participants were house officers (64.4%) and responded from JSMU (61.4%) and. The highest frequency for acceptable infection control measures was observed for injection safety precautions (96.2%) followed by hand hygiene (86.4%), use of PPE (77.3%), patient screening (58.3%) and environmental cleaning (56.1%). On individual items, poor practice was observed for ventilation system in clinics (38.6%), hand washing before wearing gloves (43.2%), use of N-95 masks or powered air-purifying respirators, disinfecting the clinical contact surfaces (54.5%) and covering surfaces that cannot be cleaned (67.4%).Conclusion: Infection control practices were unsatisfactory in terms of COVID-19 patient triaging and screening, use of N-95 masks during aerosol procedures and disinfection of surrounding objects after attending the patient